2022
DOI: 10.1159/000524606
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hemoperfusion in Severe and Critical Cases of COVID-19

Abstract: <b><i>Introduction:</i></b> Uncontrolled overproduction of inflammatory mediators is predominantly observed in patients with severe COVID-19. The excessive immune response gives rise to multiple organ dysfunction. Implementing extracorporeal therapies may be useful in omitting inflammatory mediators and supporting different organ systems. We aimed to investigate the effectiveness of hemoperfusion in combination with standard therapy in critically ill COVID-19 patients. <b><i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…The mortality rate of our patients who received MV support was 88.2% at the end of the first month, while the mortality rate was 94.1% at the end of the third month. In the study of Darazam et al, the mortality rate was 67.3% in the patients who underwent hemoperfusion, while the mortality rate in the control group was 89.0% [39].…”
Section: Discussionmentioning
confidence: 92%
“…The mortality rate of our patients who received MV support was 88.2% at the end of the first month, while the mortality rate was 94.1% at the end of the third month. In the study of Darazam et al, the mortality rate was 67.3% in the patients who underwent hemoperfusion, while the mortality rate in the control group was 89.0% [39].…”
Section: Discussionmentioning
confidence: 92%
“…The pooled results demonstrated that HAT in critically ill patients with COVID-19 significantly decreased mortality at the longest follow-up compared with conventional therapy. Hemoadsorption therapy was reported to have a positive effect on clinical indicators and a significant improvement in mortality in five of the included studies (30–32,34,41). Similar results were observed by Soleimani et al (12) and Lebreton et al (40), all of which indicated a lower mortality rate of patients with severe COVID-19 receiving hemoadsorption therapy, with no statistical significance difference observed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 446 studies were excluded after screening the title and abstract, according to the inclusion and exclusion criteria, resulting in 23 studies that underwent full-text assessment. Finally, 14 published studies and 2 ongoing trials were enrolled in this systematic living review and meta-analysis (12,13,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations